From Physical Activity Intention to Behavior: The Moderation Role of Mental Toughness Among College Students and Wage Earners - Cao, Zhenfeng; Yang, Yongtao; Ding, Weiwei; Huang, Zhijian (Frontiers in Psychology, 2021)
This study explored the correlation between mental toughness (MT) and physical activity (PA), and the moderation role between PA intention and subsequent behavior among college students and wage earners. Five hundred ninety-one college students (251 male, 340 female) aged from 19 to 24 and 285 (157 male, 127 female) wage earners aged from 27 to 58 recruited from seven colleges and five cities in China. A Theory of Planned Behavior (TPB) questionnaire, MT Inventory, and the International PA Questionnaire was completed online. Results showed that attitudes, subjective norms, and perceived behavioral control explained 46.5 and 38.3% variance in PA intention among college students and wage earners separately. Intention predicted PA behavior significantly among college students and wage earners. Structural equation modeling indicated that the TPB model and the moderation model have an adequate to good fit except the TPB model among wage earners. MT was positively correlated with PA among college students and wage earners and had a significant moderation role in intention-behavior gap among college students and partially affected the transfer of PA intention to behavior among college students. Individuals with high MT had high levels of PA regardless of intention, while PA of those with low MT was low and unstable. Future research should further explore the correlation between intention and PA and the moderation role of MT in different populations using a longitudinal study in order to better understand the correlation between intention and PA, and the transition from intention to PA and better guidance PA intervention to promote PA.